1993
DOI: 10.1073/pnas.90.21.9998
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of functional organization within rat barrel cortex using intrinsic signal optical imaging through a thinned skull.

Abstract: We used optical imaging of intrinsic signals to characterize the functional representations of mystacial vibrissae (whiskers) in rat somatosensory cortex. Stimulation of individual whiskers for 2 s at 5 Hz resulted in a discrete area of functional activity in the cortex. Images of whisker representations were collected both through the dura and through a thinned skull. We characterized the functional representation of a whisker both spatially and temporally with twodimensional images and three-dimensional surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
117
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(132 citation statements)
references
References 25 publications
12
117
0
Order By: Relevance
“…In agreement with previous reports, tactile stimulation of a single facial whisker produced spatially localized optical signals centered on the principal barrel and extending well beyond one cortical column (18). Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous reports, tactile stimulation of a single facial whisker produced spatially localized optical signals centered on the principal barrel and extending well beyond one cortical column (18). Fig.…”
Section: Resultssupporting
confidence: 92%
“…The relatively large spatial extent of the hemodynamic response is in agreement with previous optical imaging studies (18). Although spiking activity after a deflection of a single whisker is largely restricted to a small number of neighboring barrel columns (35), voltage-sensitive dye imaging shows that neuronal activity after a brief deflection of a single whisker spreads from the principal barrel column to cover a large part of the Barrel cortex (23).…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, the activation area observed before ischemia agrees well with the literature, considering that the distance between adjacent whisker barrels is about 400 to 500 mm (Masino et al, 1993), and the CBF response is less localized compared with hemoglobin changes and oxidative metabolism (Weber et al, 2004). One of our principle findings is that the activation area in response to functional stimulation is significantly reduced after the ischemic insult.…”
Section: Discussionsupporting
confidence: 91%
“…Although it has been verified that early negative 610 nm signals or deoxygenation signals offer a small point-spread function and high spatial specificity to activated columnar structures (Frostig et al, 1990;Masino et al, 1993;Malonek and Grinvald, 1996;Thompson et al, 2003), it is unclear how accurately the response magnitude reflects the magnitude of evoked neural activity. The use of differential subtraction methods in optical imaging studies presupposes not only colocalization but also a linear relationship between optical signals and underlying neuronal activity.…”
Section: Early Oxygenation Signals and Neuronal Activitymentioning
confidence: 99%